Diego Rivera - Foard, Sheila Wood. (Philadelphia : Chelsea House, 2003)
Examines the life and work of early twentieth-century Mexican artist Diego Rivera, best known for his murals in government offices, schools, and other public buildings.
Artist at the crossroads -- The magnificent painter -- Rivera in Europe -- Revolutionary muralist -- Early murals -- Marriage of the "Red" artists -- Artist of all Mexico -- Final touches.
Includes bibliographical references and index.
8.6
5-8
Keywords: Rivera, Diego, -- 1886-1957.; Artists -- Mexico -- Biography